The influence of the duration luminal experimental seizure - Sal y Rosas, Federio (1940)
Investigating the attack duration cardiazol 119 hits. brought about under the luminal influenia and other sedatives in complete deprivation in epileptic and non-epileptic patients, we have verified the following: 1 The attacks produced under the luminal ineluencia are of longer duration than those made in this deprivation barbiturate. 2 The study of the distribution of the attacks on the scale of time reveals: a) increased frequency levels long time with consecutive decline in the medium and short time; b) elevation of the medium, dominant values ​​and maximum frequency. 3 These changes under the action of luminal are verified both epileptic and non-epileptic, considering all of the cases. And its magnitude is directly related to the degree of illumination. 4 These changes are presented accurately, and interestingly even in nonepileptic, including all clinical type any side. In epileptics, such action is equally intense and regulate the essential form (comprising the largest number of cases); but irregular and shown, in some aspect, contradictory in the symptomatic form, perhaps due to the reduced material experience. 5.-phase experiment (in which the same patients are subjected to two-stage cadiazolización opposite sense without luminal luminal, have found that the attack experimental duration is longer in phase, whether or luminalizada deprivation, which leads us to believe that this amplification may be due to the influence of cardiazolización itself, which is more intense in the second phase than in the first. the text is a partial demonstration of this hypothesis by comparing what we call primitive and secondary attacks to finish:.. not less interesting similarity of luminalización binomials and deprivation, and convulsive states and non-convulsive diseases, under the terms of the duration of cardiazol attack latter revealed in our previous work led us to hypothesize that the residence experimental amplification attack is linked to a factor convulsiógeno and now, with the new finding emerged from this work, we extended considering the following two points:. 1. luminalización and diseases critical-engine type exercises some form Likewise action on the nervous system; and 2 this action rotates around convulsiógenos factors, taking into account the pharmacology of the luminal against seizure symptom, it is mpas of the Epilepsy opposite sense factor. These and other issues raised by new facts discovered unexpectedly, need to be specified and located in terms of other aspects of the unprovoked attack and other views Cardiazol experimentation with, and we're actuamente unfolding, with a view to give a set theoretical interpretation.